Circulating tumor DNA for breast cancer: Review of active clinical trials. (2022) - Baksh, Mizba; Mahajan, Biraaj; Dufresne, Maria M; Shoukry, Mira M; Nussbaum, Samuel; Abbaszadeh-Kasbi, Ali; Ashary, Mohammed; Vandenberg, Jonathan; Gabriel, Emmanuel M
Highlights: Research studies are currently investigating biomarkers for early detection of breast cancer. Interventional liquid biopsy aims at guiding choice of therapy and treatment modifications. Active clinical trials show how liquid biopsy is being utilized and its clinical implications. Circulating tumor DNA has been used to detect tumor burden and minimal residual disease in metastatic breast cancer. There are multiple uses of ctDNA that can help physicians in early detection and treatment of localized breast cancer and. Abstract: Background: The new diagnostic concept of liquid biopsy is based on the analysis of circulating tumor cells (CTCs) and cell-free DNA (ctDNA). In addition to providing a more comprehensive view of the tumor characteristics including molecular variations, ctDNA analysis through liquid biopsies may also allow for a non-invasive, rapid, and cost-effective identification of biomarkers for tumor detection and monitoring of tumor progression. Objective: In this review, we summarize key active clinical trial studies involving utilization of ctDNA derived from liquid biopsy in the early and metastatic breast cancer setting. With this, we also provide a brief overview of the potential future implementations of the LB technology and outlining how ctDNA analysis needs to be standardized through the performance of similar clinical studies. Methods: A review was conducted on Clinicaltrials.gov to identify active trials related to use of circulating tumor DNA (ctDNA) for breast cancer. Search terms included "breast cancer, " "liquid biopsy, " and "ctDNA." Conclusion: While LB is gaining traction in many cancer settings, its use in BC is still early and warrants more investigation in breast cancer diagnostic and treatment settings, including early detection of disease recurrence.